Malay Reservation Enacments method of securing the rights and interest of Malays in land / Maisarah Mokhtar - Mokhtar, Maisarah (Faculty of Law, 1984)
Problems in Malay Reservation land were to exist from the very day the Enactment was passed. However, it is only today that such problems are vividly seen as more and more Malay Reservations are slipping into the hands of non-Malays. Each state has exclusive Enactment to provide laws. in protecting Malay rights and interest in land by laying out prohibitions on dealings between the Malays and non-Malays. However, the enforcement of the Enactments must be read so as to suit the government policies in its bid to improve the Malays economics. Consequently Malay title or interest in such land can now be charged to non-Malay by way of security. Inspite of the flexibility in law Malay Reservation land also possesses other serious problems of very slow development rate, black-market dealings, poor locations and economical social and political weaknesses of the Malays themselves. Because the Malays are dependent on their land there is a need to stress for economic development among the Malays in General. This can be done through the intensive implementation of the New Economic Pol icy, some modifications on the customary law and the National Land Code.